Application of explanatory text writing instruction with counseling services to improve students' literacy skills - Syamsul Anwar; Yusran Hasymi; Husni Husni (Jurnal Konseling dan Pendidikan, 2026)
This study explores the integration of explanatory text writing instruction with counseling services to enhance students' literacy skills. Using a qualitative method through a library research approach, the study systematically reviews existing literature to evaluate how these two interventions contribute to improving writing competence and academic engagement. The review synthesizes findings from various studies published between 2016 and 2025, examining the effectiveness of structured writing instruction and psychosocial support in educational contexts. The synthesized literature suggests that when combined, writing instruction and counseling services are reported to contribute to improvements in students' writing skills, motivation, and emotional resilience. Moreover, digital tools and culturally responsive teaching practices are also reported in the literature to enhance the effectiveness of these interventions in diverse educational contexts. However, challenges related to resource limitations and insufficient professional training for teachers and counselors were identified. The study concludes that a holistic educational approach, integrating both cognitive and emotional support, is important for fostering sustained literacy development. Nevertheless, the review also highlights limitations in the current evidence base, as many existing studies are short-term in scope and vary in methodological rigor. Future research should therefore prioritize longitudinal and more rigorous empirical designs, as well as the integration of digital counseling tools, to better understand the long-term impact of these combined interventions on students’ literacy outcomes.